Building m-health technology to promote breastfeeding - Jéssika Roberta Firme de Moura Santos; Maria Alzete de Lima; Ana Larissa Gomes Machado; Edina Araújo Rodrigues Oliveira; Adriele de Almeida Brito; Milena Leite Veloso; Luisa Helena de Oliveira Lima (Revista de Enfermagem da UFPI)
Objective: to develop an m-health technology to promote breastfeeding in nursing mothers. Methods: methodological study, carried out from February 2020 to July 2021. Technological development application, following Pressman's prototyping model. The content was based on the precepts of Meaningful Learning, elaborated through a situational diagnosis and an integrative review, which guided the compilation of information and guidelines. It has a Computer Program Registration Certificate from the National Institute of Industrial Property (Process No. BR512021002438-9). Results: the application is entitled "Amamente" (Breastfeeding), and consists of the visual identity of the nursing mother, the welcome screen, and the "We want to meet you" screen. This is followed by eleven interactive interfaces for ouaccessing guidance and information such as breastfeeding; milk production; my breasts; signs of correct positioning; signs of correct latch-on; milk extraction; breast problems; signs of effective breastfeeding; when not to breastfeed; mom's space and references. Conclusion: the technology was built successfully and its final version brought together national and international scientific recommendations. "Amamente" can be used as a resource with potential reach and favorable to the process of health education and future interventions for mothers during breastfeeding.